Effects of Long Chain Omega-3 Fatty Acid Supplementation on the Lipoprotein Oxylipin Response to an Inflammatory Challenge in Humans (P08-127-19). (24th October 2019) - Walker, Rachel; Richter, Chesney; Skulas-Ray, Ann; Kris-Etherton, Penny; Jensen, Gordon; Shearer, Gregory
Abstract: Objectives: Oxylipins are derived from polyunsaturated fatty acids (PUFAs) and mediate inflammatory responses, but the time-dependent response of oxylipins to an acute inflammatory challenge in humans is unknown. Although omega-3 acid ethyl esters (O3EEs) reduce plasma triglycerides, it is unclear whether they alter the response of oxylipins in triglyceride rich lipoproteins (TGRLs). We investigated the effect of 3.4 g/d O3EEs on the oxylipin response to an inflammatory challenge. Methods: Healthy young men ( N = 16) received either placebo or 3.4 g/d O3EEs for 8–12 weeks in a crossover study design. After each treatment period, subjects underwent a low-dose endotoxin challenge (0.6 ng lipopolysaccharide (LPS)/kg body weight). Plasma samples were collected at baseline and 1, 2, 4, 8, 24, 48, 72, and 168 hours after LPS injection. TGRLs were separated from plasma, and esterified oxylipins were hydrolyzed and quantified by LC-MS/MS. Changes over time were assessed by the use of mixed models with repeated measures. Data is reported as mean (95% CI). Results: The peak total oxylipin response occurred at 4 hours after LPS injection, with the exception of hydroxyeicosatetraenoic acids (HETEs). Regardless of treatment, the peak concentration of HETEs occurred at 2 hours. This timing differed from that of hydroxyoctadecadienoic acids (HODEs), which peaked at 4 hours ( P = 0.004). Of the omega-3 derived oxylipins, O3EE treatment significantly increased hydroxyeicosapentaenoic acids (HEPEs) by 356% (133%, 792%), hydroxydocosahexaenoic acids (HDoHEs) by 172% (34%, 452%), and epoxydocosapentaeinoic acids (EpDPEs) by 316% (76%, 887%) compared to placebo at 4 hours after LPS challenge ( P < 0.007). Additionally, O3EE treatment also significantly altered the timing of the HEPE response (pinteraction = 0.004). Conclusions: The time-dependent TGRL oxylipin response to inflammatory challenge differs according to oxylipin class, and the timing and magnitude of the response can be altered by O3EE treatment. This is may be a molecular explanation of the anti-inflammatory and pro-resolving effects of O3EEs. Funding Sources: Pronova BioPharma; Penn State Clinical & Translational Research Institute, NIH/NCATS Grant # UL1 TR000127; Penn State College of Health and Human Development. Supporting Tables, Images and/or Graphs